2005
DOI: 10.1007/s10592-005-9006-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic management of the red squirrel, Sciurus vulgaris: a practical approach to regional conservation

Abstract: The progressive decline in red squirrel (Sciurus vulgaris) numbers in Wales has led to conservation and reintroduction projects being established on the island of Anglesey. The recovery of the island's remnant wild population was initially successful, however concern remained over potential loss of genetic diversity resulting from an observed demographic bottleneck. We used mitochondrial DNA (mtDNA) control region sequences and six microsatellite loci to assess current levels of genetic variation in the popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 42 publications
(45 reference statements)
1
26
2
1
Order By: Relevance
“…In addressing the first aim of this study; to determine whether the Irish population is distinct from that found in Britain, these results found, as described in previous genetic studies of red squirrels (Barratt et al 1999;Hale et al 2004;Ogden et al 2005), no clear geographic partitioning of haplotypes (Fig. 2), meaning that the Irish red squirrel population is not an ESU (Moritz 1994).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In addressing the first aim of this study; to determine whether the Irish population is distinct from that found in Britain, these results found, as described in previous genetic studies of red squirrels (Barratt et al 1999;Hale et al 2004;Ogden et al 2005), no clear geographic partitioning of haplotypes (Fig. 2), meaning that the Irish red squirrel population is not an ESU (Moritz 1994).…”
Section: Discussionsupporting
confidence: 56%
“…Sequences were then aligned with published red squirrel sequence data (AY178452-AY178479, Hale et al 2004) in CLUSTAL_X (Thompson et al 1997), and novel haplotypes identified with the MS EXCEL SEQUENCE TOOLKIT (Stephen Park, UCD). These haplotypes were further compared to other published data (AF1110001-AF111027, Barratt et al 1999; AY372270-AY534120, AY534120-AY534121, Ogden et al 2005) which overlapped with our sequences by 175 bp, to ensure that the haplotypes were indeed novel along this area of overlap, Fig. 1 Locations of collection sites of samples used in this study; the three regions to which the contemporary samples were assigned are also shown.…”
Section: Discussionmentioning
confidence: 98%
“…Compared to our study, only one island population of S. vulgaris in Pentraeth, Anglesey, U.K. (Ogden et al 2005), the endangered Delmarva fox squirrel (S. niger cinereus, see Lance et al 2003), and the endangered Vancouver Island marmot (M. vancouverensis, Kruckenhauser et al 2009) had similar or even lower levels of genetic diversity.…”
Section: Genetic Diversitycontrasting
confidence: 84%
“…Nowhere is this more evident than in reintroduction projects, where typically fewer than 100 individuals and sometimes less than 20 individuals, are released to found new populations (e.g. Greth and Schwede 1993;Ogden et al 2005). Arabian oryx represent an extreme case in which the numbers of founders for both private collections and the world herd stock were remarkably low.…”
Section: Introductionmentioning
confidence: 99%